Iron Deficiency Anemia, Cystitis, and Bacterial Vaginosis Increase the Risk for Developing Preterm Labor - Janet Sumampouw; I Ketut Suwiyoga; Ketut S. Negara (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To prove the association of iron deficiency anemia, cystitis, and bacterial vaginosis as risk factors for preterm labor.Methods: This study was an observational case-control study conducted at the Polyclinic and IRD of Obstetrics and Gynecology Sanglah Denpasar General Hospital Center between September and December 2015. The sample selection was done by consecutive sampling with total sample as many as 35 case samples (women with preterm pregnancy) and 35 control samples (women with aterm pregnancy).Results: Pregnant mothers with iron deficiency anemia had 4 fold increased risk of developing preterm labor (OR = 4.04, 95% CI = 1.15 to 14.16, p = 0.023) compared to those without iron deficiency anemia. Pregnant mothers with cystitis had 4 fold increased risk of preterm labor (OR = 4.00, 95% CI = 1.25 to 12.80, p = 0.016) compared to those without cystitis. Pregnant mothers with bacterial vaginosis had 3 fold increased risk of preterm frequency (OR = 3.24, 95% CI = 1.22 to 8.63, p = 0.017) compared to those without bacterial vaginosis.Conclusion: Iron deficiency anemia, cystitis, and bacterial vaginosis increase the risk for developing preterm labor.[Indones J Obstet Gynecol 2017; 5-2: 73-76]Keywords: bacterial vaginosis, cystitis, iron deficiency anemia, preterm labor